2015
DOI: 10.1021/acs.joc.5b01278
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tricyclic Spiranoid Lactones via I2/Sm(II)- and I2/Pd(0)-Mediated Cyclizations of a Common Cycloalkylmethylene Precursor

Abstract: A general synthesis of phylogenetically and structurally different tricyclic angularly fused spiranoid lactones, frequently observed as scaffold segments of various biochemical compounds and drugs of natural origin, is demonstrated via controlled cyclization of simple and easily accessible cycloalkylmethylene key precursors. The rapid composition of the key architecture yields an assembly of stable bicyclic iodolactones, which are converted to form a wide range of angularly fused tricyclic scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The next and largely intuitive step towards the formation of the desired framework was to subject iodolactone 3 to the C−C bond‐forming cyclization conditions. For this purpose, the diastereoisomeric lactones 3 a and b were separated and individually submitted to the cross‐coupling reaction in the presence of the Pd 0 ‐SIMes catalyst to generate a tricyclic product (Scheme , the cross‐coupling route) . As anticipated, compound 3 a gave rise to target 6 , the sought‐after tricyclic spirofuranone 5/5/5…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The next and largely intuitive step towards the formation of the desired framework was to subject iodolactone 3 to the C−C bond‐forming cyclization conditions. For this purpose, the diastereoisomeric lactones 3 a and b were separated and individually submitted to the cross‐coupling reaction in the presence of the Pd 0 ‐SIMes catalyst to generate a tricyclic product (Scheme , the cross‐coupling route) . As anticipated, compound 3 a gave rise to target 6 , the sought‐after tricyclic spirofuranone 5/5/5…”
Section: Resultsmentioning
confidence: 96%
“…To design a basic platform for the synthesis of a compact 5/5/5 scaffold, we prepared bicyclic iodolactone 3 , which is believed to be a critical intermediate for the construction of the corresponding spirofuranone (delivered from precursor I in 83 %, 67:33 d.r. ; Scheme ) . The next and largely intuitive step towards the formation of the desired framework was to subject iodolactone 3 to the C−C bond‐forming cyclization conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The transformation (Scheme 21, B) showed good functional group tolerance and a broad substrate scope, overcoming the difficulties of previously reported stepwise lactonization-Heck type cyclization approaches 68 → 70 (Scheme 21, A). 41 As part of the study, rarely reported palladium-catalyzed 4-exo-trig Heck type cyclizations were demonstrated, providing rapid access to oxaspiro-octanones 75 (Scheme 21, C).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…The stepwise strategy (Scheme 2) is based on the notion that, in the presence of I 2 or Br 2 and a metal-ligand system, the key cycloalkylmethylene precursor 3 generates lactone intermediate 4, and further undergoes an intramolecular cyclization to form the corresponding tricyclic spiranoid lactones 5. 8 Our previously reported sequence was designed to allow simplified access (first collective protocol) to a wide range of tricyclic spirolactones. Even though it is clearly the shortest sequence reported to date, some of its characteristics are ought to be mended.…”
mentioning
confidence: 99%